Arthur Rackham : A Life with Illustration - Hamilton, James, author 427240 (London: Pavilion Books Limited, 1990)
A fascinating insight into the personality, career and work of one of the world's most collectable illustratorsFilled with enchanting pictures and authoritative textIn this fascinating book, art historian James Hamilton examines the work and life of the illustrator Arthur Rackham. Rackham's illustrations for works such as Rip Van Winkle, Peter Pan in Kensington Gardens, Alice in Wonderland and A Midsummer Night's Dream have attained the classic status of the writings themselves – indeed, in some cases they have become synonymous with them. Rackham himself, however, has previously remained a shadowy figure. As well as featuring exquisite illustrations and sketches, extracts from Rackham's correspondence and insightful commentary from James Hamilton shed new light on this much collected illustrator.